Analysis of the Influence of Money Supply, Interest Rates, and Inflation on Indonesia's Economic Growth for the Period 2006-2023 - Abdullah Harun Kemal; Ida Ayu Putri Suprapti; Irwan Suriadi (Indonesian Development Economics and Localities, 2025)
The purpose of this study is to examine the correlation between inflation, interest rates, money supply, and economic development in Indonesia from 2006 to 2023. Data collection techniques used include documentation and literature studies collected from various sources (such as files). Researchers also use the BPS and BI websites to collect data. Multiple linear regression analysis and explanatory quantitative analysis using Eviews 12 are used in this study. The study findings show that from 2006 to 2023, the amount of money in circulation, interest rates (birate), and inflation (ihk) all have an impact on the development of the Indonesian economy. However, the amount of money in circulation has a negative and insignificant effect, interest rates have a negative and insignificant impact, while inflation has a positive and significant impact.